2020
DOI: 10.1002/asia.202000700
|View full text |Cite
|
Sign up to set email alerts
|

A Macrocyclic Peptide Library with a Structurally Constrained Cyclopropane‐containing Building Block Leads to Thiol‐independent Inhibitors of Phosphoglycerate Mutase

Abstract: Here we report the construction of an mRNA‐encoded library of thioether‐closed macrocyclic peptides by using an N‐chloroacetyl‐cyclopropane‐containing exotic initiator whose structure is more constrained than the ordinary N‐chloroacetyl‐α‐amino acid initiators. The use of such an initiator has led to a macrocycle library with significantly suppressed population of lariat‐shaped species compared with the conventional libraries. We previously used a conventional library and identified a small lariat thioether‐ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Despite our successful design and screening, the cyclization chemistry is largely limited to the thioether linkage. 37 , 38 Preparing new analogues of the cyclic peptide using different cyclization methods could further influence their cell permeability, activity, and pharmacological properties. Hence, we synthesized the propargylated form of our lead peptides, D wLYLDDSGDWWIG(Prop)G, 3 ; and GWFDDLYWFVAY(Prop)G, 4 , and cyclized them using our current Au(I)-mediated cyclization method to obtain the corresponding cyclic peptides 5 and 6 , respectively ( Figure 5 a).…”
Section: Resultsmentioning
confidence: 99%
“…Despite our successful design and screening, the cyclization chemistry is largely limited to the thioether linkage. 37 , 38 Preparing new analogues of the cyclic peptide using different cyclization methods could further influence their cell permeability, activity, and pharmacological properties. Hence, we synthesized the propargylated form of our lead peptides, D wLYLDDSGDWWIG(Prop)G, 3 ; and GWFDDLYWFVAY(Prop)G, 4 , and cyclized them using our current Au(I)-mediated cyclization method to obtain the corresponding cyclic peptides 5 and 6 , respectively ( Figure 5 a).…”
Section: Resultsmentioning
confidence: 99%
“…The resulting K D range predicted by binding-energy consolidation ( 37 ) from the product of the core K D (2–100 nM) and metal-ion–coordinating K D (IC 50 > 500 μM) sequence ( Ac- YGTC-CONH 2 ) is estimated between 10 −14 and 10 −12 M. While this theoretical affinity is ∼100-fold higher than the range we observe, the experimental findings are significantly greater than the sum of the interactions and more in line with binding-energy enhancements seen in multisubstrate adduct inhibitors ( 38 ). Recently, we have identified purely macrocyclic, nonthiol-containing iPGM inhibitors, suggesting broad potential for inhibitor development ( 39 ). However, being devoid of an apparent transition metal-ion–coordinating moiety places the potency of these new cyclic peptides in the range of Ce-2d.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a lariat-shaped structure with a small N-terminal cycle and a C-terminal tail with free downstream cysteine(s) is formed as a major product. On the other hand, installing a structurally constrained chloroacyl-containing initiator residue (e.g., N-chloroacyl-γCp-Phe dipeptide, where γCp is a cyclopropane-containing γ-amino acid) preferentially affords large peptide macrocycles [95]. Head-to-head comparison of screening experiments using mRNA-displayed peptide libraries differing in initiator residues confirmed that distinct cyclic peptides are enriched against the same molecular target [95].…”
Section: In Vitro Molecular Evolutionmentioning
confidence: 96%
“…On the other hand, installing a structurally constrained chloroacyl-containing initiator residue (e.g., N-chloroacyl-γCp-Phe dipeptide, where γCp is a cyclopropane-containing γ-amino acid) preferentially affords large peptide macrocycles [95]. Head-to-head comparison of screening experiments using mRNA-displayed peptide libraries differing in initiator residues confirmed that distinct cyclic peptides are enriched against the same molecular target [95]. Moreover, regioselective cyclization with distal cysteine residues may be exploited for subsequent CLIPSing of free cysteines, allowing bridging of cyclized peptides.…”
Section: In Vitro Molecular Evolutionmentioning
confidence: 99%